The Economic Case for Nature : A Global Earth-Economy Model to Assess Development Policy Pathways - Johnson, Justin Andrew; Ruta, Giovanni; Baldos, Uris; Cervigni, Raffaello; Chonabayashi, Shun; Corong, Erwin; Gavryliuk, Olga; Gerber, James; Hertel, Thomas; Nootenboom, Christopher; Polasky, Stephen (World Bank, Washington, DC, 2021)
The Economic Case for Nature is part of a series of papers by the World Bank that lays out the economic rationale for investing in nature and recognizes how economies rely on nature for services that are largely underpriced. This report presents a first-of-its-kind global integrated ecosystem-economy modelling exercise to assess economic policy responses to the global biodiversity crisis. Modeling the interaction between nature’s services and the global economy to 2030, the report points to a range and combination of policy scenarios available to reduce the impact of nature’s loss on economies. This modeling framework represents an important steppingstone towards ‘nature-smart’ decision-making, as it seeks to support policymakers who face complex tradeoffs involving the management of natural capital, and hence achieving growth that is resilient and inclusive.